Persistent hymen with mucus accumulation in a crossbred heifer - S. Satheshkumar; S. Raja; S. Senthil Kumar; V. Prabaharan; R. Rajkumar; M. Saravanan; N. Premalatha (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Hymen normally appears as a circular constriction between vagina and vulva. However varying degrees of persistence, from thin band to complete imperforate structure, may occur in all species due to segmental defects of paramesonephric ducts (Roberts, 1971). Complete obliteration of vaginal canal due to imperforate hymen was reported earlier in crossbred (Kumar et al., 2017), pure bred (Kumar et al., 2020) and buffalo heifers (Singh et al., 2010 and Kumar et al., 2016) with varying degrees of mucus accumulation. The present report places on record a case of persistent hymen with voluminous mucus accumulation in a crossbred heifer. Vaginal speculum was passed and held in position against the septum. A sterile intrauterine catheter was passed through the septum and thick cloudy mucus started flowing out following the catheterization. To facilitate easy and complete evacuation, suction pump was employed and about 15 litres of mucus was removed. After the fluid evacuation, per rectal examination revealed that the uterine contours palpable within the pelvic cavity. Ultrasonographic examination showed a clear band of tissue across the vaginal canal posterior to cervical region.